INTERPOLASI YURISPRUDENSI TERAPEUTIK DENGAN PROBLEM-SOLVING COURT DALAM PERLUASAN MAKNA KEADILAN RESTORATIF - Hozeng, Pratiwi; Sugianto, Fajar; Rahayu, Sekar Wiji (DiH: Jurnal Ilmu Hukum, 2021)
AbstractThe law has limited restrictions on such arbitrary treatment and the people have rights which are rights owned by the authorities, especially in accessing the law. Restorative justice is an important approach to improve people's welfare, but its implementation is still limited. Research wants to see how the meaning is in the application of restorative justice. The research was conducted by applying the normative-empirical method by examining at the same time the opportunities for further development of the field of study. Regulations that do not cover all cases that arise in society make the multidisciplinary field of science important and consider, the similarity of the restorative meaning of justice provides an opportunity to carry out a new, more complex definition overall by guaranteeing the welfare and equality of the people before the lawKeywords: psychology law; restorative justice; therapeutic jurisprudenceAbstrak Hukum telah secara tegas membatasi perlakuan sewenang-wenang tersebut serta rakyat memiliki hak yang setara sebagaimana yang dimiliki oleh para penguasa, khususnya dalam mengakses hukum. Keadilan restoratif menjadi pendekatan yang penting untuk mempertahankan kesejahteraan rakyat namun pengimplemantasian masih terbatas. Penelitian ingin melihat bagaimana pemaknaan dalam penerapan keadilan restoratif. Penelitian dilakukan dengan menerapkan metode normatif-Empiris dengan mengkaji sekaligus membuka kesempatan bidang kajian yang dapat dikembangkan berikutnya. Peraturan perundang-undangan yang berlaku belum mencakup seluruh perkara yang timbul dalam masyarakat menjadikan bidang multidisplin ilmu menjadi penting dan dipertimbangkan, keserupaan makna keadilan restoratif memberikan peluang dalam mengusung pendefinisian baru yang lebih kompleks menyeluruh dengan menjamin kesejahteraan dan kesetaraan rakyat dimata hukum.